The needs assessment of hospitalized cancer patients' undergoing chemotherapy at oncology wards of Hospital University Sains Malaysia (HUSM) - Asaari, Siti Nurzawani (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2012)
Determined the need of hospitalized cancer patients undergoing chemotherapy is crucial in order to provide a holistic nursing care. From the researcher knowledge, there have been no published studies to determine the needs of hospitalized cancer patients undergoing chemotherapy in Malaysia. The aim of this study was to assess the needs of hospitalised cancer patients undergoing chemotherapy at oncology wards of Hospital Universiti Sains Malaysia (HUSM). Significant difference between gender and different aged groups towards needs level also was determined. A cross sectional survey on cancer patients undergoing chemotherapy (n=73) at oncology wards of HUSM was done by using a self-administered structured questionnaire. Data was analyzed using the Statistical Package Social Science (SPSS) software version 19.0. From this study population (n=73), 39 were male (39%) and 34 were nurses (46.6%). The Independent T-test had been performed. However, from the finding, there were no significant difference (t (71) = 1.91, p = 0.060) was found between male (mean= 87. 74, S.D.= 13.52) and females (mean= 80.53, S.D. = 14.19) in terms of their needs level. The finding suggests that there are no sex differences in the level of needs for the hospitalized cancer patients that undergoing chemotherapy. Result finding from One way ANOV A showed that, the needs level among the six aged group were significantly different F (5,67) = 3.16, p = 0.01. Since the probability of error is < 0.05, the null hypothesis is rejected. The mean score for group 31-40 years was the lowest compared to the other aged group. Therefore, the patients within the aged 31 to 40 years had the lowest needs level. While the mean score for group 61-70 years (M=90.27, S.D =8.40, n=22) was the highest compared to the others aged group. The finding show that hospitalized cancer patients undergoing chemotherapy among the aged 61 to 70 years had the highest needs level.